2019
DOI: 10.1186/s12963-019-0191-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the magnitude of the economic, health and population effects of palm cooking oil consumption: an integrated modelling approach with Thailand as a case study

Abstract: Background Palm oil’s high yields, consequent low cost and highly versatile properties as a cooking oil and food ingredient have resulted in its thorough infiltration of the food sector in some countries. Longitudinal studies have associated palm oil’s high saturated fatty acid content with non-communicable disease, but neither the economic or disease burdens have been assessed previously. Methods This novel palm oil-focussed disease burden assessment employs a fully in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…SFA are undesirable fatty acids associated with increased cholesterol in the blood. Literature has found that a specific cholesterol ratio to HDL in the bloodstream is a more precise heart disease indicator than just LDL concentration [ 30 ]. This study also stated that individual fatty acids could affect the ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SFA are undesirable fatty acids associated with increased cholesterol in the blood. Literature has found that a specific cholesterol ratio to HDL in the bloodstream is a more precise heart disease indicator than just LDL concentration [ 30 ]. This study also stated that individual fatty acids could affect the ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The USFA content of rapeseed oils accounts for approximately 90% of the fatty acid composition [ 22 , 30 ]. This was evident for rapeseed oils tested in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Although many plant parts may yield oil, in commercial practice, oil is extracted primarily from seeds (Philip, 2022;Zhou et al, 2020;Ying et al, 2020;Purcaro et al, 2016;Kumar et al, 2016). Brahmi et al (2020); Keogh-Brown et al (2018) reported that vegetable oils are of great economic importance to human, industrially, vegetable oils are also used as ingredients or components in many manufactured products. Many other uses of ORIGINAL RESEARCH ARTICLE vegetable oils have been recorded by (Norzahir et al, 2019;Owuna, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studying the effect of these interactions is as complex as it is important, and the bar to this kind of cross-disciplinary policy analysis has previously been the technical difficulty of integrating models which simultaneously capture all of these elements together with their dynamic feedback effects. However, previous applications of computable general equilibrium (CGE) models in the context of HIV/AIDS, 17 health co-benefits of GHD reduction strategies, 18 and dietary change [19][20][21] have advanced the level of complexity and use of these models in a health context, and the tool we developed for this study demonstrates that full integration of models is possible. Furthermore, its utility is illustrated in analyses of various scenarios for future economic growth and scaling up of interventions.…”
Section: Introductionmentioning
confidence: 99%